Non-invasive Prenatal Determination of Fetal Maturity - Dzikova, Elena; Dimitrov, Goran; Stojceva-Taneva, Olivera (Македонско лекарско друштво / Walter de Gruyter GmbH, 2016)
The prenatal prediction of fetal maturity is very important, since neonatal respiratory distress syndrome (RDS) is one of the biggest causes of neonatal mortality. Our aim was to investigate a new non-invasive method for prediction of fetal maturity and to determine in which group according to gestational age of the fetus, the treatment works the best and in which cases it is necessary to be repeated. Methods. We examined 60 patients (30 with impending preterm delivery, divided in 3 groups: 28-30, 30-32, and 32-34 gestational weeks and 30 controls), at the University Clinic for Gynecology and Obstetrics, Medical Faculty, University “Ss. Cyril and Methodius”, Skopje, R. Macedonia. Fetal maturity was examined using ultrasound histogram from fetal lungs and liver, correlated with gestational age and postpartum RDS. Where possible, we performed amniocentesis for lamellar body count (LBC) to correlate our results with the current invasive method for prediction of fetal maturity. Results. Pre-therapy investigation showed a strong fetal immaturity in 28-32 weeks of gestation and less evident fetal immaturity in 32-34 weeks of gestation. Seventy-two hours post-treatment, fetal maturation was low in the first group, higher in the second and the highest in the third group. Amniocentesis for LBC showed correlation with the ultrasound results. Postpartum results were correlated with pre-delivery ultrasound and showed significance of p <0.05. Conclusion. The results obtained in our study were with high significance, and they were in correlation with other similar studies. However, more extensive investigations should be made to replace the current invasive technique.